PENGARUH GOOD CORPORATE GOVERNANCE, PENGENDALIAN INTERNAL DAN AUDIT INTERNAL TERHADAP PENCEGAHAN KECURANGAN ( FRAUD ) ( STUDI KASUS PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2021-2024) - Redemptus Doni Malo; Yudas Tadius Andi Candra (ITB AAS Indonesia Surakarta, 2026)
This study was conducted to determine and analyze the influence of good corporate governance, internal control, and internal audit on fraud prevention (a case study of banking companies listed on the Indonesia Stock Exchange for the period 2021-2024). The study population was all banking companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2024. The test results indicate that Good Corporate Governance (GCG) has a significant and strong influence in reducing the likelihood of fraud. The results indicate that internal control has no significant influence on fraud prevention, although the regression coefficient indicates a negative direction. Internal audit has been shown to make a significant contribution to preventing fraud in banking companies. The results of simultaneous testing indicate that all three independent variables together have a significant influence on fraud prevention.